Ethnography of Code-Switching: A Classroom-Based Study in Bilingual (English–Arabic) Islamic Boarding Schools - Ahmadi, Ahmadi (Tarling : Journal of Language Education, 2025)
This research explores the phenomenon of code-switching in bilingual (English–Arabic) classrooms within Islamic boarding schools (pesantren) in Indonesia. Utilizing a classroom ethnography approach, the study investigates how language alternation occurs during daily instructional activities and how it serves various pedagogical, religious, and sociocultural purposes. Data were collected through classroom observations, audio recordings, and in-depth interviews with teachers and students at two pesantren that implement both international (English-based) and Islamic (Arabic-based) curricula. The findings demonstrate that code-switching is systematically employed by teachers and learners as a strategic tool to clarify concepts, manage classroom discourse, and reinforce religious identity. Rather than being perceived as linguistic interference, it functions as an intentional and context-sensitive practice shaped by the multilingual and multicultural nature of pesantren education. In this setting, Arabic often marks moments of religious significance, such as quoting Qur'anic verses or conveying Islamic values, while English is used to navigate academic content, instructions, and modern discourse. This interplay reflects a hybrid identity cultivated in pesantren students one that harmonizes Islamic tradition with global engagement. The study highlights the value of code-switching as a communicative and pedagogical asset in Islamic bilingual education, challenging deficit views of language mixing. It offers practical implications for teacher training, bilingual curriculum design, and sociolinguistic awareness in religious schooling. These findings encourage educators and policymakers to view code-switching not as a challenge, but as a resource that enriches the learning process in multilingual Islamic contexts.